Modification of CaO Catalyst From Chicken Eggshell With Wet Impregnation Method for Two-Stage Process of Biodiesel from Tamanu Oil - Kanesya Najah Abidin; Gymnastiar, Reza (Jurnal Serambi Engineering, 2025)
Egg production from laying hens in Indonesia is so high that if the egg shells produced are not used properly, they will produce waste. Chicken eggshell waste has a high mineral content, one of which is calcium. Calcium can be utilized as a heterogeneous catalyst which can be used in making renewable energy such as biodiesel. Biodiesel is an alternative energy that is being widely developed because it can be an environmentally friendly alternative to diesel engine fuel. This research aims to determine biodiesel obtained from tamanu oil (Calophyllum inophyllum) by etherification and transesterification processes using a catalyst modified from egg shells using a wet impregnation method using alkaline potassium hydroxide. The catalyst used is the catalyst with the highest alkalinity for making biodiesel. The biodiesel produced had the highest yield of 76.9040% with a density value of 0.94981 gr/ml and a viscosity of 4.11412 cSt.